The extravagantly modified dorsal setae of Daidalotarsonemus oliveirai and Excelsotarsonemus caravelis (Acari: Prostigmata: Tarsonemidae) females: Ultrastructure and functional implications - Di Palma, Antonella; Kitajima, Elliot W.; Lofego, Antonio C. (Arthropod structure & development, 2021)
The genera Daidalotarsonemus De Leon and Excelsotarsonemus Ochoa & Naskrecki are mainly characterized, in the females, by the presence of sculpturing on the dorsal shields and by highly modified dorsal setae, greatly enlarged, laminar or sail-shaped. Moreover, both genera are characterized by abundant cerotegument all over the body and on the modified setae (d, e, f) with the presence of fungi, lichens, and bacteria accumulating. The peculiar morphology of the dorsal setae in these two genera has suggested they might have other functions beside the sensory one. Ultrastructural observations using scanning and transmission electron microscopy techniques revealed that, albeit extravagantly modified, these dorsal setae should act as mechanoreceptors in agreement with most of the previous observations in mites. The morphological modifications of the setae d, e, and f (pronounced cup shape of setae e and enlarged shaft with concave longitudinal strips of setae d and f) suggest they play, in addition to the tactile function, a storage role and dispersive role for fungal spores collected by the mite while moving in the humid environment. Moreover, the modified setae d, e, and f inserted on elevated sockets are probably movable by the action of dorso-ventral muscles; thus, mites might use their sail-shape to become airborne. In addition, the body dorso-ventral muscles observed inserting close to the elevated seta e sockets suggest the mite might also lift these cup-like setae to spread the fungal particles on the body or over adjacent vegetation as well. Biological and feeding studies are necessary to better understand the role such fungi might play in the mite life cycle. •Posterior dorsal setae are highly modified in Daidalotarsonemus and Excelsotarsonemus females.•These setae don't have a hair shaft, are greatly enlarged or laminar.•According to their ultrastructure they are typical mechanoreceptive sensilla.•Their modified shaft seems to serve to store and carry fungal spores.•Mites seem able to rise the setae thanks to the contraction of dorso-ventral muscles attaching close to the seta sockets.